The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fmolb.2021.673977
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Droplets in the Pathogenesis of Hereditary Spastic Paraplegia

Abstract: Hereditary spastic paraplegias (HSPs) are genetically heterogeneous conditions caused by the progressive dying back of the longest axons in the central nervous system, the corticospinal axons. A wealth of data in the last decade has unraveled disturbances of lipid droplet (LD) biogenesis, maturation, turnover and contact sites in cellular and animal models with perturbed expression and function of HSP proteins. As ubiquitous organelles that segregate neutral lipid into a phospholipid monolayer, LDs are at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 161 publications
(248 reference statements)
1
16
0
Order By: Relevance
“…It has been established that mammalian cells (including both neurons and glia) can accumulate lipid droplets in pathological conditions and in modeling various neurodegenerative disorders, such as Huntington’s and Alzheimer’s disease [ 128 , 129 , 130 , 131 , 132 ], as well as HSP [ 133 , 134 , 135 , 136 ]. Several HSP-associated proteins have been shown to affect LD dynamics: spartin, spastin, atlastin-1, seipin and REEP1 [ 135 , 137 , 138 , 139 , 140 , 141 ]. A recent study has shown that the C-terminal region of NTE/PNPLA6, but not the full-length protein, could also be physically attached to LDs with high affinity, inducing the clustering of the latter [ 142 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that mammalian cells (including both neurons and glia) can accumulate lipid droplets in pathological conditions and in modeling various neurodegenerative disorders, such as Huntington’s and Alzheimer’s disease [ 128 , 129 , 130 , 131 , 132 ], as well as HSP [ 133 , 134 , 135 , 136 ]. Several HSP-associated proteins have been shown to affect LD dynamics: spartin, spastin, atlastin-1, seipin and REEP1 [ 135 , 137 , 138 , 139 , 140 , 141 ]. A recent study has shown that the C-terminal region of NTE/PNPLA6, but not the full-length protein, could also be physically attached to LDs with high affinity, inducing the clustering of the latter [ 142 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it recently emerged that dysfunction of one cellular organelle or function can have a deep impact on other cellular functions (Figure 3). For example, proteins implicated in the cytoskeleton dynamics such as spastin, can participate in organellar shaping particularly in ER morphogenesis, or modulate the formation of lipid droplets (LD) which can be considered as the intersection of these pathways with lipid metabolism in the pathogenesis of HSP (Figure 3) (Papadopoulos et al, 2015;Tadepalle and Rugarli, 2021). Furthermore, loss of spatacsin (SPG11) that promotes tubule formation on lysosomes also affects sphingolipid metabolism and leads to impairment of cholesterol recycling from lysosomes resulting in their accumulation and decrease in the cholesterol content of the plasma membrane which allowed us to include SPG11 as the 17th HSP form involving lipid metabolism (Boutry et al, 2018;.…”
Section: Pathways Involved In Hsp Pathogenesismentioning
confidence: 99%
“…[AR: ichthyotic keratoderma, spasticity, hypomyelination and dysmorphic features (IKSHD)], ELOVL4 [AR: ichthyosis, intellectual disability and spastic quadriplegia (ISQMR); AD: SCA34, Stargardt disease 3 ((STGD3)], ALDH3A2 [Sjögren-Larsson Syndrome (SLS)]. This long list of examples provides clear evidence that the existing phenotypic classes of neurogenetic disorders need to be reconsidered Tadepalle and Rugarli, 2021). Various types of lipids are involved in spastic neurodegeneration including precursor lipids as cholesterol and fatty acids as well as complex lipids like phospholipids and sphingolipids.…”
Section: Pathways Involved In Hsp Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence have identified lipid homeostasis disruption in cellular and animal models of HSP (reviewed in [ 19 , 84 ]). To examine whether Arl6IP1 functionally contributes to lipid homeostasis in vivo, we investigated LD organisation within axonal bundles of control and Arl6IP1 KO flies.…”
Section: Resultsmentioning
confidence: 99%